"New Atheism And Its Global Impact: A Study Of Contemporary Movements And Their Influence" - Muhammad Ajmal , Dr. Aqeel Ahmed (Migration Letters, 2024)
The emergence of New Atheism, characterized by its assertive critique of religion and advocacy for secularism, has significantly impacted global discourse on faith and belief systems. This research article examines the rise of New Atheism from an Islamic perspective, focusing on how contemporary movements within this ideology influence religious and cultural dynamics worldwide. New Atheism, represented by prominent figures such [1]as Richard Dawkins, Sam Harris, and Christopher Hitchens, challenges traditional religious beliefs, including those in Islam, through a combination of scientific arguments and philosophical critiques. From an Islamic viewpoint, this paper explores how New Atheism’s critique of religious doctrines is perceived and addressed within Islamic theology and philosophy. It assesses the responses of Muslim scholars and communities to the challenges posed by New Atheist arguments, including debates on the compatibility of faith with science, morality without religion, and the historical and cultural contributions of Islam.The study also investigates the broader implications of New Atheism’s global reach, particularly how it influences interfaith dialogue and the perception of Islam in the public sphere. It evaluates the impact of New Atheism on Muslim identity and the strategies adopted by Islamic thinkers to engage with and counteract the critiques of contemporary atheistic movements.By analyzing these interactions, the research highlights the complex interplay between New Atheism and Islamic thought, offering insights into how modern atheistic ideologies shape and are shaped by global religious and cultural landscapes. This examination aims to contribute to a nuanced understanding of the dynamics between secular and religious worldviews in the 21st century.